2017
DOI: 10.20944/preprints201702.0103.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fructose Consumption in the Development of Obesity and the Effects of Different Protocols of Physical Exercise on the Hepatic Metabolism

Abstract: Fructose consumption has been growing exponentially and, concomitant with this, the increase in the incidence of obesity and associated complications has followed the same behavior.Studies indicate that fructose may be a carbohydrate with greater obesogenic potential than other sugars. In this context, the liver seems to be a key organ for understanding the deleterious health effects promoted by fructose consumption. Fructose promotes complications in glucose metabolism, accumulation of triacylglycerol in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…Fructose has been a part of human diet for thousands of years, and it is found in highest concentrations in high fructose corn syrup (55% to 90% fructose), honey (40% fructose), and fruits (up to 7.6% fructose) (Raatz, Johnson, & Picklo, ; Sun & Empie, ). In the last decades, high fructose corn syrup as an inexpensive sweetener is widely used in food processing industry, and this causes a grave increase (30%) in consumption of fructose (Pereira et al., ; Tappy & Lê, ). With the increase of fructose consumption, nonalcoholic fatty liver disease (NAFLD) in world has increased to unintelligible levels (Nomura & Yamanouchi, ; Suwannaphet, Meeprom, Yibchokanun, & Adisakwattana, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fructose has been a part of human diet for thousands of years, and it is found in highest concentrations in high fructose corn syrup (55% to 90% fructose), honey (40% fructose), and fruits (up to 7.6% fructose) (Raatz, Johnson, & Picklo, ; Sun & Empie, ). In the last decades, high fructose corn syrup as an inexpensive sweetener is widely used in food processing industry, and this causes a grave increase (30%) in consumption of fructose (Pereira et al., ; Tappy & Lê, ). With the increase of fructose consumption, nonalcoholic fatty liver disease (NAFLD) in world has increased to unintelligible levels (Nomura & Yamanouchi, ; Suwannaphet, Meeprom, Yibchokanun, & Adisakwattana, ).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to battle these metabolic and health problems, physical exercise has been widely used as a non‐pharmacological strategy. It is well established that a physically active lifestyle helps prevent and treat various of these health problems . Our study proposes that chronic physical exercise acts positively on this metabolic process and prevents hepatic fat accumulation with CLK2 protein participation.…”
Section: Discussionmentioning
confidence: 72%
“…Due to the high rates of individuals with hepatic fat accumulation, pharmaceutical, and nutritional strategies were developed to curb the damage of this disorder. Physical exercise has been extensively recommended for providing relevant actions in the battle against hepatic fat accumulation and metabolic disorders …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High fructose intake may induce metabolic disorders, but it is not clear whether this is associated with weight gain. Studies indicated that fructose consumption may be associated with weight gain and causes to the development of obesity . On the contrary, some studies were explained that fructose intake did not directly increase body weight .…”
Section: Discussionmentioning
confidence: 99%